2012
DOI: 10.1111/j.1528-1167.2012.03720.x
|View full text |Cite
|
Sign up to set email alerts
|

Rhythmic neuronal activity in S2 somatosensory and insular cortices contribute to the initiation of absence‐related spike‐and‐wave discharges

Abstract: SUMMARYPurpose: The origin of bilateral synchronous spike-andwave discharges (SWDs) that underlie absence seizures has been widely debated. Studies in genetic rodent models suggest that SWDs originate from a restricted region in the somatosensory cortex. The properties of this initiation site remain unknown. Our goal was to characterize the interictal, preictal and ictal neuronal activity in the primary and secondary cortical regions (S1, S2) and in the adjacent insular cortex (IC) in Genetic Absence Epilepsy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
54
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 42 publications
7
54
0
Order By: Relevance
“…Similarly, in the first study providing evidence for a cortical focus in WAG/Rij rats using an electrocorticography (ECoG) grid on SI, Meeren et al (2002) systematically found the leading sites of seizures on the most posterior and lateral electrodes. Still, as shown by Zheng et al (2012) in GAERS rats, it is not excluded that the focus is actually located in more lateral regions. Our planar MEAs showed variable patterns across animals, probably due to the local somatotopy of SI and to small differences in implantation sites.…”
Section: Network-mediated Entrainment Of the Epileptogenic Focus Leadmentioning
confidence: 97%
See 2 more Smart Citations
“…Similarly, in the first study providing evidence for a cortical focus in WAG/Rij rats using an electrocorticography (ECoG) grid on SI, Meeren et al (2002) systematically found the leading sites of seizures on the most posterior and lateral electrodes. Still, as shown by Zheng et al (2012) in GAERS rats, it is not excluded that the focus is actually located in more lateral regions. Our planar MEAs showed variable patterns across animals, probably due to the local somatotopy of SI and to small differences in implantation sites.…”
Section: Network-mediated Entrainment Of the Epileptogenic Focus Leadmentioning
confidence: 97%
“…In that study, it is unknown if afterdischarges originated from the stimulated region, which could explain the differences in duration between SI and MI, or if they recruited the natural focus as shown here. Another study by Zheng et al (2012) has shown that electrical stimulation (2-s trains, 7 Hz) of SI, SII, and insular cortex (IC) induces self-sustained SWDs in Genetic Absence Epilepsy Rats from Strasbourg (GAERS), with lower current thresholds for SII and IC. Again, because of the lack of array recordings, the authors did not investigate the precise spatiotemporal dynamics of the induced SWDs.…”
Section: Network-mediated Entrainment Of the Epileptogenic Focus Leadmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that the transitions between sleep and waking are controlled by neuromodulatory systems (Steriade et al, 1993b;Saper, 2006;Lee and Dan, 2012). During slow-wave sleep or anesthesia, when neuromodulatory tone is low, the cortical network generates slow waves that, at an intracellular level, appear as an alternation of hyperpolarized or silent states with minimal levels of synaptic activity and depolarized or active states with high levels of synaptic activities (Steriade et al, 2001;Timofeev et al, 2001a;Chauvette et al, 2011). An elevated level of neuromodulators during wakefulness and rapid eye movement (REM) sleep strongly reduces the activity of the membrane potassium channels, which depolarizes multiple types of cortical neurons (Krnjević et al, 1971;McCormick, 1992;Hasselmo and McGaughy, 2004;Steriade and McCarley, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned above, a bilaterally present, hyperexcitable, focal area within the deep layers (V and VI) of the perioral somatosensory cortex (S1po) has been identified as the seizure onset zone (Meeren et al, 2002;Polack et al, 2007) or rather near in the S2 or insular cortex (Zheng et al, 2012) and the necessity of this focal area(s) for SWD generation has been validated by several independent research groups exploiting different experimental techniques (for review see (van Luijtelaar and Sitnikova, 2006). It can be noted, that such a focal cortical onset zone, although not located within the somatosensory cortex, but rather in fronto-temporal cortical regions, has also been identified in children with absence epilepsy in several EEG, MEG (magnetoencephalogram) and EEG-fMRI studies (Holmes et al, 2004;Moeller et al, 2008;Westmijse et al, 2009).…”
Section: Brain Regions Of Interestmentioning
confidence: 99%